PENGARUH PRODUKSI, KONSUMSI DAN HARGA KEDELAI NASIONAL TERHADAP IMPOR KEDELAI DI INDONESIA - Assifah, Puteri (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
In comparison to the major soybean-producing nations in the globe, Indonesia's soybean production is still in a relatively early stage of development. The demand for domestic agricultural products is rising along with the population growth and rising per capita consumption. There is a gap between the demand for and supply of domestic agricultural products as a result of the rising demand for agricultural products not being met by rising local soybean production. Time series analysis is a quantitative method used in this study. Data was collected between 2010 and 2019. According to the study's findings, neither consumption nor production have an impact on imports. While imports of soybeans are impacted by the price variable.